Mimesis in Mobile Legends hero narratives: Recontextualizing Indonesian literary works - Lukman Hakim; Yuyun Wahyu Izzati Surya; Sutinah Sutinah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study examines Mobile Legends as a popular digital medium that recontextualizes Indonesian literary and folkloric narratives through game characters. Previous studies on Mobile Legends have mainly focused on visual representation, cultural identity, gender, and player behavior, while the relation between Indonesian literary sources and game narratives through mimetic and narrative analysis remains less explored. This study aims to reveal the mimetic patterns and narrative recontextualization of Gatotkaca and Kadita in Mobile Legends. Using a qualitative interpretive method, this study applies Abrams’s mimetic perspective and Greimas’s narrative analysis to examine character lore, hero descriptions, visual-audiovisual elements, and intertextual relations with the narratives of Gatotkaca, Nyi Roro Kidul, Putri Kandita, the Mahabharata, wayang traditions, and related Indonesian literary-folkloric sources. The findings show that Gatotkaca and Kadita are transformed through three levels of mimesis: idea, sensory-cultural form, and artistic-digital work. Gatotkaca is recontextualized from a wayang heroic figure into a ludic subject oriented toward defense, attack, and competitive gameplay, while Kadita is transformed from a mythic sea queen figure into a mage hero whose sacred maritime power becomes a playable ability. This study contributes by integrating Abrams’s mimesis and Greimas’s narrative structure to explain how Indonesian literary figures are reshaped into narrative, visual, and ludic functions in mobile game media.